Technology Acceptance and Readiness among different Generations of Urban Touists - Smith, Melanie K.; Coronel Padilla, Monica Fabiola (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER Several motivators and inhibitors for technology acceptance and readiness have been identified, however, propensity to use digital tools can vary according to different factors, one of them being the users’ age. This study seeks to explore the technology acceptance and readiness of different generations of tourists in an urban destination. METHODOLOGY This qualitative study comprised 94 face-to-face interviews conducted during autumn 2019 and the spring of 2020 (before COVID-19) to foreign visitors from different age groups close to the main attractions in Budapest, Hungary. Interviews gathered visitors’ thoughts, experiences, and perceptions about tourism and technology. Interviews were audio recorded, transcribed and content analysed applying a deductive approach. MOST IMPORTANT RESULTS Baby Boomers are more inhibited than motivated in terms of technology readiness due to the lack of technical knowledge and challenges of use. Generation X are more optimistic about the usage of technologies driven by convenience and social influence. Younger generations use a wider range of digital tools while travelling due to greater levels of optimism and innovativeness. However, some participants from Generation Y1 and X consciously limit the use of technologies as they consider them disruptive. Findings also show that motivators tend to be more closely related to utilitarian rather than hedonic factors for all generations. Smartphones and Google Maps are the most used digital tools. This novel study focuses on different models and approaches for technology acceptance and readiness from a generational perspective exploring the so-called ‘digital gap’. Furthermore, this study explores the correlation between different determinants of the proposed models. The context of an urban destination is also relatively novel, as many previous studies have focused rather on individual sites. RECOMMENDATIONS Urban destinations should facilitate conditions to encourage acceptance and readiness of technology among urban tourists. This not only includes digital infrastructure (e.g. WI-FI), but digital solutions and apps (e.g. tour guides in different languages) designed to attract different target markets (i.e. generations).